Surgical Management of Extrafollicular Variant of Adenomatoid Odontogenic Tumor in the Maxillary Posterior Region - Gerardo La Monaca; Nicola Pranno; Cira Rosaria Tiziana di Gioia; Giorgio Pompa; Iole Vozza; Maria Paola Cristalli (Case Reports in Dentistry)
Background. Adenomatoid odontogenic tumor (AOT) is a relatively uncommon benign neoplasm of odontogenic epithelial origin, accounting for less than 5% of odontogenic tumors. Case Report. The reported case describes morphological characteristics, clinical course, radiographic and histopathological features, and surgical therapy of an extrafollicular variant of AOT in the maxillary posterior region. An asymptomatic swelling on the left side in the posterior region of the maxilla, gradually increased since approximately 12 months, developed in a 16-year-old Caucasian female patient. Radiographic images revealed a well-defined, unilocular radiolucency, with some small foci of radiopacity inside, and root resorption of the first and second molars. On the base of the histological examination of the specimen retrieved by incisional biopsy, the diagnosis of AOT was made, and the conservative surgical enucleation of the lesion was performed. Discussion. The present case was reported in agreement with an extensive review, in which it was recommended to discontinue reporting classic follicular cases because their clinicopathological profile was well-known, but to continue reporting well-documented cases of the extrafollicular variant, with indication of the exact position. Conclusion. The present case was reported in order to expand the knowledge about the clinical behavior and surgical treatment of the extrafollicular variant of AOT.